Contemporary Zakat Management Strategy: Integrating Productive and Consumptive Distribution for Mustahik Empowerment in Three Indonesian Provinces - Liky Faizal; Rodiah Nur, Efa; Yasir Fauzi, Moh.; Harapandi Dahri Syahrum (Universitas Islam Negeri Raden Intan Lampung, 2026)
Zakat management must evolve from traditional charity to a contemporary development mechanism to fulfill its potential in poverty alleviation. This study aims to comparatively analyze the implementation of the Contemporary Integrated Zakat Distribution Model utilized by the National Zakat Agency (BAZNAS) across three provinces, Lampung, South Sumatra, and Banten, and to empirically measure its impact on the welfare transformation of pre-prosperous families (mustahik). A multi-location case study approach, employing a Mixed-Method framework, was adopted. Qualitative data were gathered through in-depth interviews with BAZNAS managers and mustahik beneficiaries, supported by the analysis of internal reports and policies. Quantitative data on change the economic status of mustahik post-intervention were analyzed descriptively and comparatively to validate the model's effectiveness. The findings confirm that BAZNAS successfully implements an Integrated Model that systematically combines consumptive support (for immediate needs) with productive empowerment (capital, skills training, and human capital investment). This model demonstrates a significant positive impact on sustainable welfare. The quantitative analysis is highly conclusive: the percentage of households classified as pre-prosperous declined substantially, specifically by 31% in Lampung, 35% in South Sumatra, and 40% in Banten. The highest transformation rate in Banten is linked to its strategic focus on educational investments (One Family One Scholar). The research validates that a contemporary, integrated approach to Zakat distribution is effective in achieving socio-economic transformation, thereby supporting the objectives of maqāsid al-sharīah. The results provide an empirical basis for Zakat institutions to prioritize high-impact human capital programs for sustainable poverty exit